Electrochemical device and electronic device
By designing the first coating and positive electrode material layer containing inorganic particles and carbon nanotubes in the positive electrode sheet of the lithium-ion battery, the problem of short circuit in the nailing process is solved, and the low-temperature cycle performance and fast charging performance are improved, achieving better safety and performance.
Patent Information
- Application Number
- CN202510033849.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
During the nailing process of lithium-ion batteries, short circuits are prone to occur between the positive electrode and negative electrode plates, resulting in insufficient safety performance and poor circulation and fast charging performance under low temperature conditions.
An electrochemical device is designed, wherein the positive electrode sheet includes a positive electrode current collector, a first coating and a positive electrode material layer. The first coating is composed of inorganic particles, and the positive electrode material layer contains the first conductive agent as the first carbon nanotube. By regulating the length and diameter of the carbon nanotube, the ion transmission rate and conductivity are optimized, and the fast charging performance and low-temperature cycling performance are improved. At the same time, the high diaphragm resistance of the first coating increases the short circuit resistance and improves the safety performance of nail penetration.
The electrochemical device reduces the risk of short circuit in nail-through tests, improves low-temperature cycle performance and fast charging performance, and takes into account safety performance, cycle performance and fast charging performance.
Smart Images

Figure CN119833555A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices (such as lithium-ion batteries) have become popular in our daily lives with the development of science and technology. Lithium-ion batteries have entered our daily lives along with the advancement of science and technology and the improvement of environmental protection requirements. With the widespread popularity of lithium-ion batteries, their service life has been increasingly valued by users. Consumers, after-sales service, battery manufacturers and lithium battery manufacturers have all put forward new requirements for battery safety performance.
[0003] However, with the rapid popularization of lithium-ion batteries, the technology for their product safety is not mature. During use, the positive and negative electrodes of lithium-ion batteries often come into contact with each other during the nailing process, or the positive and negative electrodes are connected by nails, resulting in internal short circuits. As people pay more and more attention to the safety performance of lithium-ion batteries, the market is in urgent need of a lithium-ion battery with good nailing safety performance. Summary of the invention
[0004] The purpose of the present application is to provide an electrochemical device and an electronic device to improve the nail penetration safety performance, low-temperature cycle performance and fast charging performance of the electrochemical device.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides an electrochemical device, which includes a positive electrode plate, the positive electrode plate includes a positive electrode collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode collector; the first coating includes inorganic particles, and the inorganic particles include at least one of nano-boehmite, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide or zinc oxide; the positive electrode material layer includes a first conductive agent, and the first conductive agent includes a first carbon nanotube; the length of the first carbon nanotube is 2μm to 5μm, and the diameter of the first carbon nanotube is 2nm to 100nm; the ion migration number of the positive electrode material layer is 0.4 to 0.47. The electrochemical device includes the above-mentioned structure and the first conductive agent of the positive electrode material layer satisfies the above-mentioned characteristics, which is beneficial to provide a transmission channel for matching electrons and ions for the positive electrode plate, thereby improving the ion transmission rate, further improving the charging rate, and improving the fast charging performance and low-temperature cycle performance; at the same time, when the first coating satisfies the above-mentioned characteristics, it has a higher membrane resistance, which is beneficial to increase the short-circuit resistance, reduce the dangerous short-circuit points between the positive electrode plate and the negative electrode plate during the nail penetration test, reduce the heat power generated by the short circuit, and while improving the nail penetration safety performance of the electrochemical device, match the conductivity of the positive electrode material layer, thereby improving the low-temperature cycle performance and fast charging performance of the electrochemical device, so that the electrochemical device provided by the present application can take into account the nail penetration safety performance, low-temperature cycle performance and fast charging performance.
[0007] In one embodiment of the present application, the length of the first carbon nanotube is 2 μm to 4 μm, and / or the diameter of the first carbon nanotube is 20 nm to 80 nm. By adjusting the length of the first carbon nanotube and / or the diameter of the first carbon nanotube within the above range, the conductivity of the positive electrode material layer is adjusted to a suitable value, while improving the safety performance of the electrochemical device, the low temperature cycle performance and fast charging performance of the electrochemical device are further improved.
[0008] In one embodiment of the present application, based on the mass of the positive electrode material layer, the mass percentage of the first carbon nanotube is 0.5% to 2.5%. The mass percentage of the first carbon nanotube is within the above range, which is conducive to improving the electronic conductivity, and the conductivity of the first coating of the positive electrode sheet and the positive electrode material layer matches each other, while improving the safety performance of the electrochemical device, further improving the low temperature cycle performance and fast charging performance of the electrochemical device.
[0009] In one embodiment of the present application, based on the mass of the positive electrode material layer, the mass percentage of the first conductive agent is 0.6% to 3.1%. By adjusting the mass percentage of the first conductive agent within the above range, the conductivity of the positive electrode material layer is adjusted to a suitable value, and the conductivity of the first coating of the positive electrode sheet matches the conductivity of the positive electrode material layer, while improving the safety performance of the electrochemical device, the low temperature cycle performance and fast charging performance of the electrochemical device are further improved.
[0010] In one embodiment of the present application, the positive electrode material layer further includes a second conductive agent, and the second conductive agent includes at least one of conductive carbon black or activated carbon; based on the mass of the positive electrode material layer, the mass percentage of the second conductive agent is 1.4% to 2.8%. When the type and mass percentage of the second conductive agent are within the above range, the electronic conductivity and ionic conductivity of the positive electrode material layer are improved, and while improving the safety performance of the electrochemical device, the low-temperature cycle performance and fast charging performance of the electrochemical device are further improved.
[0011] In one embodiment of the present application, the first coating also includes a first binder and a third conductive agent, and the Dv90 of the inorganic particles is 200nm to 1000nm, preferably 400nm to 600nm. By regulating the Dv90 of the inorganic particles within the above range, the inorganic particles form a dense coating on at least one surface of the positive electrode current collector, and the first coating can wrap the metal burrs that may be generated by the positive electrode current collector in the nail penetration test under abnormal conditions such as nail penetration and impact, enhance the protection of the positive electrode current collector during the nail penetration test, reduce the possibility of internal short circuits in electrochemical devices, reduce the probability of thermal runaway caused by local overheating of electrochemical devices, and further improve the nail penetration safety performance of electrochemical devices.
[0012] In one embodiment of the present application, the thickness of the first coating is 0.2 μm to 2 μm, preferably 0.5 μm to 1.25 μm. By adjusting the thickness of the first coating within the above range, the first coating is thicker and has higher mechanical strength, which is beneficial to protecting the positive electrode collector during the nail penetration test, reducing the probability of internal short circuit of the electrochemical device, and reducing the probability of thermal runaway caused by local overheating of the electrochemical device, and further improving the nail penetration safety performance of the electrochemical device.
[0013] In one embodiment of the present application, the ratio of the thickness of the first coating layer to the thickness of the positive electrode material layer is 0.18% to 2.2%. By adjusting the ratio of the thickness of the first coating layer to the thickness of the positive electrode material layer within the above range, it is beneficial to adjust the appropriate ion transmission path, increase the ion transmission rate, and further improve the fast charging performance of the electrochemical device.
[0014] In one embodiment of the present application, the mass percentage of the inorganic particles is 80% to 94.5% based on the mass of the first coating. When the mass percentage of the inorganic particles is within the above range, the first coating has a higher film resistance, which is beneficial to increase the short-circuit resistance, reduce the dangerous short-circuit point between the positive electrode sheet and the negative electrode sheet during the nail penetration test, reduce the heat power generated by the short circuit, and further improve the nail penetration safety performance of the electrochemical device.
[0015] In one embodiment of the present application, the first binder includes a water-soluble polymer metal salt; based on the mass of the first coating, the mass percentage of the first binder is 0.5% to 15%. By regulating the first binder to be selected from the above materials and the mass percentage within the above range, the water-soluble polymer metal salt has good hydrophilicity, which is conducive to the transmission of electrons and ions, and is conducive to improving the dynamic performance and low-temperature cycle performance; the water-soluble polymer metal salt has a large specific surface area and can be highly dispersed after contacting water. It is used as the first binder in the first coating layer, which can improve the tensile strength of the first coating. At the same time, the water-soluble polymer metal salt has many polar functional groups and functional groups that can form hydrogen bonds, and forms a strong hydrogen bond with the oxide layer on the surface of the positive electrode collector, which is conducive to improving the bonding force between the first coating and the positive electrode collector, and improving the nail penetration safety performance of the electrochemical device; at the same time, the degree of peeling of the first coating and the positive electrode collector during the cycle is reduced, the interface contact impedance during the cycle is improved, and the low-temperature cycle performance and cycle life of the electrochemical device are further improved.
[0016] In one embodiment of the present application, the metal element in the water-soluble polymer metal salt includes at least one of lithium, sodium, potassium, rubidium, cesium, francium, beryllium, barium, strontium, calcium or magnesium; the polymer in the water-soluble polymer metal salt includes at least one of polyacrylic acid, carboxymethyl cellulose, polyacrylonitrile or styrene butadiene. The metal elements and polymers in the water-soluble polymer metal salt are within the scope of the present application, which are conducive to improving the transmission performance of electrons and ions, making their electronic conductivity and ion conductivity better than non-water-soluble high molecular polymers such as polyvinylidene fluoride and polyvinylidene chloride, improving mass transfer kinetics, and further improving the kinetic performance and low-temperature cycle performance of electrochemical devices.
[0017] In one embodiment of the present application, the water-soluble polymer metal salt includes at least one of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, calcium polyacrylate, magnesium polyacrylate, rubidium polyacrylate, cesium polyacrylate, francium polyacrylate, barium polyacrylate, strontium polyacrylate, lithium carboxymethyl cellulose, beryllium carboxymethyl cellulose or sodium carboxymethyl cellulose. The type of water-soluble polymer metal salt is within the scope of the present application, further improving the nail penetration safety performance, low temperature cycle performance and kinetic performance of the electrochemical device.
[0018] In one embodiment of the present application, the third conductive agent includes at least one of conductive carbon black, activated carbon, carbon nanotubes or carbon nanofibers; based on the mass of the first coating, the mass percentage of the third conductive agent is 0.7% to 5%. When the type and mass percentage of the third conductive agent are within the above range, the first coating has high short-circuit resistance and good conductivity, further improving the low-temperature cycle performance of the electrochemical device.
[0019] In one embodiment of the present application, in the first coating layer, within the range of 4 μm×4 μm in a scanning electron microscope image at a magnification of 30,000 times, the particle size of the secondary particles of the third conductive agent is less than 50 nm. The particle size of the secondary particles of the third conductive agent is within the above range, indicating that the third conductive agent is evenly distributed in the first coating layer, has good dispersibility, can increase the density of the conductive network, and further improve the cycle and fast charging performance of the electrochemical device.
[0020] In one embodiment of the present application, the bonding force between the first coating and the positive current collector is 500N / m to 900N / m. The bonding force between the first coating and the positive current collector is within the above range, indicating that the first coating and the positive current collector have good bonding, and the first coating can wrap the metal burrs that may be generated in the current collector under abnormal conditions such as nail penetration and impact, so as to reduce the occurrence of internal short circuits in the electrochemical device, and at the same time, reduce the probability of thermal runaway or overheating combustion caused by local overheating of the electrochemical device, and further improve the nail penetration safety performance of the electrochemical device.
[0021] In one embodiment of the present application, the sheet resistance of the first coating is 200Ω to 2500Ω. The sheet resistance of the first coating is within the above range, which is conducive to increasing the short-circuit resistance, reducing the Joule heat generated instantly during the short-circuit process, reducing the risk of dangerous short circuits, and improving the safety performance of the electrochemical device.
[0022] In one embodiment of the present application, in the electrochemical impedance spectrum of the positive electrode sheet, the characteristic frequency is between 10 4 Hz to 10 6 There is an Rcont peak in the Hz range, with a characteristic frequency of 10 -1 There is an Rct peak in the range of Hz to 10Hz, and the ratio of the contact impedance of the Rcont peak to the fitting impedance of the Rct peak is 10 -5 The positive electrode sheet meets the above characteristics, and the electron transmission resistance in the conductive network is small, which improves the cycle and fast charging performance of the electrochemical device.
[0023] In one embodiment of the present application, the film resistance of the positive electrode sheet is 1Ω to 3Ω. The positive electrode sheet meets the above characteristics, which is conducive to increasing the short-circuit resistance, reducing the Joule heat generated during the short-circuit process, reducing the risk of dangerous short circuits, and improving the safety performance of the electrochemical device.
[0024] In one embodiment of the present application, the resistivity of the positive electrode material layer is 1.125×10 -5 Ω·cm to 1.875×10 -5Ω·cm. The positive electrode sheet meets the above characteristics, the positive electrode material layer has low resistance and good electronic conductivity, indicating that the electrochemical device including the positive electrode sheet of the present application has good low-temperature cycle performance and fast charging performance; at the same time, the resistance of the first coating layer is high, and the resistance difference between the two is large, which can achieve the same level of overall resistance of the positive electrode sheet, and the low-temperature cycle performance, fast charging performance and safety performance of the electrochemical device including the positive electrode sheet of the present application can be improved.
[0025] The second aspect of the present application provides an electronic device, which includes the electrochemical device described in the first aspect of the present application. The electronic device of the present application has good nail penetration safety performance, low temperature cycle performance and fast charging performance.
[0026] Beneficial effects of this application:
[0027] The present application provides an electrochemical device, which includes a positive electrode plate, the positive electrode plate includes a positive electrode collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode collector; the first coating includes inorganic particles, the inorganic particles include at least one of nano-boehmite, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide or zinc oxide; the positive electrode material layer includes a first conductive agent, the first conductive agent includes a first carbon nanotube; the length of the first carbon nanotube is 2μm to 5μm, and the tube diameter of the first carbon nanotube is 2nm to 100nm; the ion migration number of the positive electrode material layer is 0.4 to 0.47. The electrochemical device includes the above-mentioned structure and the first conductive agent of the positive electrode material layer satisfies the above-mentioned characteristics, which is beneficial to provide a transmission channel for matching electrons and ions for the positive electrode plate, thereby improving the ion transmission rate, further improving the charging rate, and improving the fast charging performance and low-temperature cycle performance; at the same time, when the first coating satisfies the above-mentioned characteristics, it has a higher membrane resistance, which is beneficial to increase the short-circuit resistance, reduce the dangerous short-circuit points between the positive electrode plate and the negative electrode plate during the nail penetration test, reduce the heat power generated by the short circuit, and while improving the nail penetration safety performance, match the conductivity of the positive electrode material layer, thereby improving the low-temperature cycle performance and fast charging performance of the electrochemical device, so that the electrochemical device provided by the present application can take into account the nail penetration safety performance, low-temperature cycle performance and fast charging performance.
[0028] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.
[0030] Figure 1 A schematic diagram of the cross-sectional structure of a positive electrode sheet along its thickness direction in one embodiment of the present application;
[0031] Figure 2 This is a scanning electron microscope image of the surface morphology of the first coating prepared in Example 1-1 of the present application;
[0032] Figure 3 This is a scanning electron microscope image of a cross section of the positive electrode sheet prepared in Example 1-1 of the present application along the thickness direction;
[0033] Figure 4 The 45°C cycle capacity retention rate change diagram of the lithium ion batteries prepared in Example 1-1, Comparative Example 2, and Comparative Example 6 in this application:
[0034] Figure 5 This is a graph showing the changes in the AC internal resistance of the positive electrode sheets prepared in Example 1-1, Comparative Example 2, and Comparative Example 6 of the present application;
[0035] Figure 6 Electrochemical impedance spectra of the positive electrode sheets prepared in Example 1-1, Comparative Example 1, and Comparative Example 6 in this application. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0037] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0038] The first aspect of the present application provides an electrochemical device, the electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive current collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive current collector. The first coating includes inorganic particles, the inorganic particles include at least one of nano-boehmite, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide or zinc oxide; the positive electrode material layer includes a first conductive agent, the first conductive agent includes a first carbon nanotube; the length of the first carbon nanotube is 2μm to 5μm, preferably, the length of the first carbon nanotube is 2μm to 4μm; the diameter of the first carbon nanotube is 2nm to 100nm, preferably, the diameter of the first carbon nanotube is 20nm to 80nm; the ion migration number of the positive electrode material layer is 0.4 to 0.47. For example, the length of the first carbon nanotube can be 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or a range consisting of any two of the values therein; the diameter of the first carbon nanotube can be 2nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm or a range consisting of any two of the values therein; the ion migration number of the positive electrode material layer can be 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47 or a range consisting of any two of the values therein. When the electrochemical device includes the above structure and the first conductive agent of the positive electrode material layer meets the above characteristics, it is beneficial to provide a transmission channel for matching electrons and ions for the positive electrode plate, thereby improving the ion transmission rate, further improving the charging rate, and improving the fast charging performance and low-temperature cycle performance of the electrochemical device; at the same time, when the first coating meets the above characteristics, it has a higher membrane resistance, which is beneficial to increase the short-circuit resistance, reduce the dangerous short-circuit points between the positive electrode plate and the negative electrode plate during the nail penetration test, reduce the heat power generated by the short circuit, and while improving the nail penetration safety performance of the electrochemical device, match the conductivity of the positive electrode material layer, improve the low-temperature cycle performance and fast charging performance of the electrochemical device, so that the electrochemical device provided by the present application can take into account the nail penetration safety performance, low-temperature cycle performance and fast charging performance.
[0039] In one embodiment of the present application, based on the mass of the positive electrode material layer, the mass percentage of the first carbon nanotube is 0.5% to 2.5%. For example, the mass percentage of the first carbon nanotube can be 0.5%, 1%, 1.5%, 2%, 2.5% or a range consisting of any two of these values. The mass percentage of the first carbon nanotube is within the above range, which is conducive to improving the electronic conductivity. The conductivity of the first coating of the positive electrode sheet matches that of the positive electrode material layer, which improves the safety performance of the electrochemical device while further improving the low-temperature cycle performance and fast charging performance of the electrochemical device.
[0040] In some embodiments of the present application, the first carbon nanotube includes at least one of a first single-walled carbon nanotube, a first multi-walled carbon nanotube, or a first carbon nanofiber. The first single-walled carbon nanotube includes a single-walled carbon nanotube (SWCNTs), the first multi-walled carbon nanotube includes a multi-walled carbon nanotube (MWCNTs), and the first carbon nanofiber includes a carbon nanofiber. The first carbon nanotube is selected from the above materials, the first conductive agent has good electronic conductivity, and the first coating of the positive electrode sheet matches the conductivity of the positive electrode material layer, while improving the safety performance of the electrochemical device, further improving the low temperature cycle performance and fast charging performance of the electrochemical device.
[0041] In some embodiments of the present application, the first conductive agent further includes a second carbon nanotube. The second carbon nanotube includes at least one of a second SWCNTs, a second MWCNTs or a second carbon nanofiber, the second SWCNTs include SWCNTs, and the second MWCNTs include MWCNTs; the length of the second carbon nanotube is 300nm to 1μm, the tube diameter is 2nm to 50nm, and the second carbon nanofiber includes carbon nanofiber. Based on the mass of the positive electrode material layer, the mass percentage of the second carbon nanotube is 0.1% to 2.6%. The first conductive agent is a composite system and meets the above characteristics, which can improve the charging rate and further improve the fast charging performance and low temperature cycle performance of the electrochemical device.
[0042] In one embodiment of the present application, based on the mass of the positive electrode material layer, the mass percentage of the first conductive agent is 0.6% to 3.1%. For example, the mass percentage of the first conductive agent can be 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 3%, 3.1% or a range consisting of any two of these values. By regulating the mass percentage of the first conductive agent within the above range, the conductivity of the positive electrode material layer is regulated to a suitable value, and the first coating of the positive electrode sheet matches the conductivity of the positive electrode material layer, while improving the safety performance of the electrochemical device, the low temperature cycle performance and fast charging performance of the electrochemical device are further improved.
[0043] In one embodiment of the present application, the positive electrode material layer also includes a second conductive agent, and the second conductive agent includes at least one of conductive carbon black or activated carbon; based on the mass of the positive electrode material layer, the mass percentage of the second conductive agent is 1.4% to 2.8%. For example, the mass percentage of the second conductive agent can be 1.4%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or a range consisting of any two of these values. When the type and mass percentage of the second conductive agent are within the above range, the electronic conductivity and ionic conductivity of the positive electrode material layer are improved, while improving the safety performance of the electrochemical device, the low temperature cycle performance and fast charging performance of the electrochemical device are further improved.
[0044] In the present application, the above-mentioned “first coating is disposed on the surface of the positive electrode current collector” means that the first coating can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of the positive electrode current collector, or a partial area of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. The above-mentioned “positive electrode material layer is disposed on the surface of the first coating away from the positive electrode current collector” can be understood by analogy. Specifically, if Figure 1 As shown, a first coating layer 12 and a positive electrode material layer 13 disposed on the first coating layer 12 away from the surface of the positive electrode collector 11 are sequentially stacked on both surfaces of the positive electrode collector 11 .
[0045] The positive electrode material layer also includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (e.g., NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate, lithium iron manganese phosphate or lithium titanate. At least one of the following. The present application has no particular restrictions on the mass percentage of the positive electrode active material in the positive electrode material layer, as long as the purpose of the present application can be achieved. Exemplarily, the mass percentage of the positive electrode active material in the positive electrode material layer may be 94% to 98%. For example, the mass percentage of the positive electrode active material may be 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98% or a range consisting of any two of the values.
[0046] The positive electrode material layer also includes a positive electrode binder. The present application has no particular restrictions on the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride. The present application has no particular restrictions on the mass percentage of the positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. Exemplarily, the mass percentage of the positive electrode binder in the positive electrode material layer can be 0.1% to 2%. For example, the mass percentage of the positive electrode binder can be 0.1%, 0.5%, 1%, 1.5%, 2% or a range consisting of any two of the values.
[0047] In the present application, the thickness of the single-sided positive electrode material layer is 70 μm to 90 μm. For example, the thickness of the single-sided positive electrode material layer can be 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, or a range consisting of any two of these values.
[0048] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0049] The thickness of the positive electrode current collector is not particularly limited in the present application, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm.
[0050] In one embodiment of the present application, the first coating also includes a first binder and a third conductive agent, and the Dv90 of the inorganic particles is 200nm to 1000nm, preferably 400nm to 600nm. For example, the Dv90 of the inorganic particles can be 200nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm or a range composed of any two of the numerical values. By regulating the Dv90 of the inorganic particles within the above range, the inorganic particles form a dense coating on at least one surface of the positive electrode current collector, and the first coating can be wrapped in the metal burrs that may be generated by the positive electrode current collector in the nail penetration test under abnormal conditions such as nail penetration and impact, and enhance the protection of the positive electrode current collector during the nail penetration test, reduce the possibility of internal short circuits in electrochemical devices, reduce the probability of thermal runaway caused by local overheating of electrochemical devices, and further improve the nail penetration safety performance of electrochemical devices.
[0051] In the present application, Dv90 means a particle size at which the volume accumulation reaches 90% from the smaller particle size side in the volume-based particle size distribution of the inorganic particles.
[0052] Inorganic particles of different particle sizes in the present application can be purchased, and the particle size testing method can refer to the "Inorganic Particle Size Testing" method provided in the "Testing Methods and Equipment" section of the present application to test the particle size of the inorganic particles and select inorganic particles of the desired particle size.
[0053] In one embodiment of the present application, the thickness of the first coating is 0.2 μm to 2 μm, preferably 0.5 μm to 1.25 μm. For example, the thickness of the first coating can be 0.2 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.25 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm or a range consisting of any two of the values. By regulating the thickness of the first coating within the above range, the thickness of the first coating is thicker and the mechanical strength is higher, which is beneficial to protect the positive electrode current collector during the nail penetration test, reduce the probability of internal short circuit of the electrochemical device, and reduce the probability of thermal runaway caused by local overheating of the electrochemical device, thereby further improving the nail penetration safety performance of the electrochemical device.
[0054] In one embodiment of the present application, the ratio of the thickness of the first coating layer to the thickness of the single-sided positive electrode material layer is 0.18% to 2.2%. For example, the ratio of the thickness of the first coating layer to the thickness of the single-sided positive electrode material layer can be 0.18%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2% or a range consisting of any two ratios thereof. By regulating the ratio of the thickness of the first coating layer to the thickness of the single-sided positive electrode material layer within the above range, it is beneficial to regulate the appropriate ion transmission path, increase the ion transmission rate, and further improve the fast charging performance of the electrochemical device.
[0055] In one embodiment of the present application, based on the mass of the first coating, the mass percentage of the inorganic particles is 80% to 94.5%. For example, the mass percentage of the inorganic particles can be 80%, 81%, 82%, 3%, 4%, 5%, 6%, 87%, 8%, 89%, 90%, 91%, 92%, 93%, 94%, 94.5% or a range consisting of any two of the values. When the mass percentage of the inorganic particles is within the above range, the first coating has a higher diaphragm resistance, which is beneficial to increase the short-circuit resistance, reduce the dangerous short-circuit points between the positive electrode sheet and the negative electrode sheet during the nail penetration test, reduce the thermal power generated by the short circuit, and further improve the nail penetration safety performance of the electrochemical device.
[0056] In one embodiment of the present application, the first binder includes a water-soluble polymer metal salt; based on the mass of the first coating, the mass percentage of the first binder is 0.5% to 15%. For example, the mass percentage of the first binder can be 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a range consisting of any two of the values. By regulating the first binder to be selected from the above materials and the mass percentage content within the above range, the water-soluble polymer metal salt has good hydrophilicity, which is conducive to the transmission of electrons and ions, and the electronic conductivity and ionic conductivity are better than those of non-water-soluble high molecular polymers such as polyvinylidene fluoride and polyvinylidene chloride. Therefore, the first coating is conducive to improving the kinetic performance of the electrochemical device and improving the low-temperature cycle performance of the electrochemical device; in addition, the water-soluble polymer metal salt has a large specific surface area and can be highly dispersed after contacting water. When used as the first binder in the first coating layer, the tensile strength of the first coating can be improved. At the same time, the water-soluble polymer metal salt has many polar functional groups and functional groups that can form hydrogen bonds, and forms strong hydrogen bonds with the oxide layer on the surface of the positive electrode collector, which is conducive to improving the bonding force between the first coating and the positive electrode collector, and improving the nail penetration safety performance of the electrochemical device; at the same time, the degree of peeling of the first coating and the positive electrode collector during the cycle is reduced, and the interface contact impedance during the cycle is improved, thereby further improving the low-temperature cycle performance and cycle life of the electrochemical device.
[0057] In one embodiment of the present application, the metal element in the water-soluble polymer metal salt includes at least one of lithium, sodium, potassium, rubidium, cesium, francium, beryllium, barium, strontium, calcium or magnesium; the polymer in the water-soluble polymer metal salt includes at least one of polyacrylic acid, carboxymethyl cellulose, polyacrylonitrile or styrene butadiene. The metal elements and polymers in the water-soluble polymer metal salt are within the scope of the present application, which are conducive to improving the transmission performance of electrons and ions, making their electronic conductivity and ion conductivity better than non-water-soluble high molecular polymers such as polyvinylidene fluoride and polyvinylidene chloride, improving mass transfer kinetics, and further improving the kinetic performance and low-temperature cycle performance of the electrochemical device.
[0058] In one embodiment of the present application, the water-soluble polymer metal salt includes at least one of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, calcium polyacrylate, magnesium polyacrylate, rubidium polyacrylate, cesium polyacrylate, francium polyacrylate, barium polyacrylate, strontium polyacrylate, lithium carboxymethyl cellulose, beryllium carboxymethyl cellulose or sodium carboxymethyl cellulose. The types of water-soluble polymer metal salts are within the scope of this application. The water-soluble polymer metal salts have good hydrophilicity, which is beneficial to the transmission of electrons and ions. The electronic conductivity and ionic conductivity are better than those of non-water-soluble high molecular polymers such as polyvinylidene fluoride and polyvinylidene chloride. Therefore, the first coating is beneficial to improving the kinetic performance of the electrochemical device and improving the low-temperature cycle performance of the electrochemical device; in addition, the water-soluble polymer metal salt has a large specific surface area and can be highly dispersed after encountering water. It is used as the first binder in the first coating layer, which can improve the tensile strength of the first coating. At the same time, the water-soluble polymer metal salt has many polar functional groups and functional groups that can form hydrogen bonds, and forms strong hydrogen bonds with the oxide layer on the surface of the positive electrode collector, which is beneficial to improving the bonding force between the first coating and the positive electrode collector, and further improving the nail penetration safety performance of the electrochemical device.
[0059] In one embodiment of the present application, the third conductive agent includes at least one of conductive carbon black, activated carbon, carbon nanotubes or carbon nanofibers; based on the mass of the first coating, the mass percentage of the third conductive agent is 0.7% to 5%. For example, the mass percentage of the third conductive agent can be 0.7%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of these values. When the type and mass percentage of the third conductive agent are within the above range, the first coating has good conductivity while having a high short-circuit resistance, further improving the low-temperature cycle performance of the electrochemical device.
[0060] In one embodiment of the present application, the first coating layer is within a range of 4 μm × 4 μm in a scanning electron microscope image with a magnification of 30,000 times, and the particle size of the secondary particles of the third conductive agent is less than 50 nm. For example, the particle size of the secondary particles of the third conductive agent can be 0.01 nm, 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 49 nm, or a range consisting of any two of these values. The particle size of the secondary particles of the third conductive agent is within the above range, indicating that the third conductive agent is evenly distributed in the first coating layer, has good dispersibility, can increase the density of the conductive network, and further improve the cycle and fast charging performance of the electrochemical device.
[0061] In the present application, the secondary particles of the third conductive agent refer to the primary particles of the third conductive agent that aggregate to form secondary particles during the preparation process of the positive electrode sheet.
[0062] In the present application, the particle size of the secondary particles of the third conductive agent may be adjusted by a ball milling dispersion process.
[0063] In one embodiment of the present application, the bonding force between the first coating and the positive current collector is 500N / m to 900N / m. For example, the bonding force between the first coating and the positive current collector can be 500N / m, 550N / m, 600N / m, 650N / m, 700N / m, 750N / m, 800N / m, 850N / m, 900N / m or a range consisting of any two values therein. The bonding force between the first coating and the positive current collector is within the above range, indicating that the first coating and the positive current collector have good bonding properties, and the first coating can wrap the metal burrs that may be generated in the current collector under abnormal conditions such as nail penetration and impact, so as to reduce the occurrence of internal short circuits in the electrochemical device, and at the same time, reduce the probability of thermal runaway or overheating of the electrochemical device due to local overheating, and further improve the nail penetration safety performance of the electrochemical device.
[0064] In one embodiment of the present application, the diaphragm resistance of the first coating is 200Ω to 2500Ω. For example, the diaphragm resistance of the first coating can be 200Ω, 300Ω, 400Ω, 600Ω, 800Ω, 1000Ω, 1200Ω, 1400Ω, 600Ω, 1800Ω, 2000Ω, 2200Ω, 2500Ω, or a range consisting of any two of these values. The diaphragm resistance of the first coating is within the above range, which is conducive to increasing the short-circuit resistance, reducing the Joule heat generated instantly during the short-circuit process, reducing the risk of dangerous short circuits, and improving the safety performance of the electrochemical device.
[0065] In one embodiment of the present application, in the electrochemical impedance spectrum of the positive electrode sheet, the characteristic frequency is between 10 4 Hz to 10 6 There is an Rcont peak in the Hz range, with a characteristic frequency of 10 -1 There is an Rct peak in the range of Hz to 10Hz, and the ratio of the contact impedance of the Rcont peak to the fitting impedance of the Rct peak is 10 -5 For example, the ratio of the contact impedance of the Rcont peak to the fitted impedance of the Rct peak can be 10 -5 , 10 -4 , 10 -3 , 0.01 or a range consisting of any two ratios thereof. The positive electrode sheet satisfies the above characteristics, and the electron transmission resistance in the conductive network is small, which improves the cycle and fast charging performance of the electrochemical device.
[0066] In one embodiment of the present application, the membrane resistance of the positive electrode sheet is 1Ω to 3Ω. For example, the membrane resistance of the positive electrode sheet can be 1Ω, 1.5Ω, 2Ω, 2.5Ω, 3Ω, or a range consisting of any two values therein. The positive electrode sheet satisfies the above characteristics, which is conducive to increasing the short-circuit resistance, reducing the Joule heat generated during the short-circuit process, reducing the risk of dangerous short circuits, and improving the safety performance of the electrochemical device.
[0067] In one embodiment of the present application, the resistivity of the positive electrode material layer is 1.125×10 -5 Ω·cm to 1.875×10 -5 Ω·cm. For example, the resistivity of the positive electrode material layer can be 1.125×10 -5 Ω·cm、1.25×10 -5 Ω·cm、1.375×10 -5 Ω·cm、1.5×10 -5 Ω·cm、1.625×10 -5 Ω·cm、1.75×10 -5 Ω·cm、1.875×10 -5 Ω·cm or a range consisting of any two of the values. The positive electrode sheet satisfies the above characteristics, the positive electrode material layer has a low resistance and good electronic conductivity, indicating that the electrochemical device including the positive electrode sheet of the present application has good low-temperature cycle performance and fast charging performance; at the same time, the resistance of the first coating is high, and the resistance difference between the two is large, which can achieve the same level of overall resistance of the positive electrode sheet, and the safety performance and low-temperature cycle performance of the electrochemical device including the positive electrode sheet of the present application can be improved.
[0068] In the present application, the first carbon nanotube can be a conventional material available on the market, and there is no particular restriction on its source, as long as the purpose of the present application can be achieved. The first carbon nanotubes with different lengths and diameters can be purchased, and the length and diameter of the first carbon nanotube can be obtained by testing, and the first carbon nanotube with the required length and diameter can be selected. Among them, the specific test method for the length and diameter of the first carbon nanotube can refer to the "Length and Diameter Test of the First Carbon Nanotube Conductive Agent" in the Test Method and Equipment section.
[0069] In the present application, the ion migration number of the positive electrode material layer can be regulated by the content of the first conductive agent, and / or the length, diameter, content, type of the first carbon nanotube, and / or the content and type of the second conductive agent. Specifically, when other parameters remain unchanged, the content of the first conductive agent increases, and the ion migration number of the positive electrode material layer increases, otherwise it decreases; when other parameters remain unchanged, the length of the first carbon nanotube increases, and the ion migration number of the positive electrode material layer increases, otherwise it decreases; when other parameters remain unchanged, the diameter of the first carbon nanotube increases, and the ion migration number of the positive electrode material layer increases, otherwise it decreases; when other parameters remain unchanged, the content of the first carbon nanotube increases, and the ion migration number of the positive electrode material layer increases, otherwise it decreases; when other parameters remain unchanged, the content of the first carbon nanotube increases, and the ion migration number of the positive electrode material layer increases, otherwise it decreases; when other parameters remain unchanged, the content of the second conductive agent increases, and the ion migration number of the positive electrode material layer increases, otherwise it decreases.
[0070] The present application does not particularly limit the method for regulating the ratio of the first coating thickness to the positive electrode material layer thickness, as long as the purpose of the present application can be achieved. For example, the ratio of the first coating thickness to the positive electrode material layer thickness can be regulated by regulating the respective values of the first coating thickness and the positive electrode material layer thickness. Among them, the thickness of the first coating can be regulated by the coating weight per unit area of the first coating, and the thickness of the positive electrode material layer can be regulated by the coating weight per unit area of the positive electrode material layer.
[0071] The present application does not particularly limit the method of regulating the sheet resistance of the first coating layer, as long as the purpose of the present application can be achieved. For example, the sheet resistance of the first coating layer can be regulated by the Dv90, type, and / or coating thickness of the inorganic particles. Specifically, when other parameters remain unchanged, the Dv90 of the inorganic particles increases, and the sheet resistance of the first coating layer decreases, and vice versa; when other parameters remain unchanged, the thickness of the first coating layer increases, and the sheet resistance of the first coating layer increases, and vice versa.
[0072] The present application has no particular restrictions on the method of regulating the film resistance of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the film resistance of the positive electrode sheet can be regulated by the content of the first conductive agent, and / or the length, diameter, content, and type of the first carbon nanotube, and / or the content and type of the second conductive agent, and / or the Dv90 and type of the inorganic particles, and / or the coating thickness of the first coating, and / or the conductivity of the positive active material. Specifically, when other parameters remain unchanged, the content of the first conductive agent increases, and the diaphragm resistance of the positive electrode sheet decreases, otherwise it increases; when other parameters remain unchanged, the length of the first carbon nanotube increases, and the diaphragm resistance of the positive electrode sheet decreases, otherwise it increases; when other parameters remain unchanged, the diameter of the first carbon nanotube increases, and the diaphragm resistance of the positive electrode sheet decreases, otherwise it increases; when other parameters remain unchanged, the content of the first carbon nanotube increases, and the diaphragm resistance of the positive electrode sheet decreases, otherwise it increases; when other parameters remain unchanged, the content of the second conductive agent increases, and the diaphragm resistance of the positive electrode sheet decreases, otherwise it increases; when other parameters remain unchanged, the conductivity of the positive active material increases, and the diaphragm resistance of the positive electrode sheet decreases, otherwise it increases; specifically, when other parameters remain unchanged, the Dv90 of the inorganic particles increases, and the diaphragm resistance of the positive electrode sheet decreases, otherwise it increases; when other parameters remain unchanged, the thickness of the first coating increases, and the diaphragm resistance of the positive electrode sheet increases, otherwise it decreases.
[0073] The present application has no particular restrictions on the manner of regulating the resistivity of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the resistivity of the positive electrode material layer can be regulated by the content of the first conductive agent, and / or the length, diameter, content, type of the first carbon nanotube, and / or the content, type, and / or the conductivity of the second conductive agent, and / or the conductivity of the positive electrode active material. Specifically, when other parameters remain unchanged, the content of the first conductive agent increases, and the resistivity of the positive electrode material layer decreases, otherwise it increases; when other parameters remain unchanged, the length of the first carbon nanotube increases, and the resistivity of the positive electrode material layer decreases, otherwise it increases; when other parameters remain unchanged, the diameter of the first carbon nanotube increases, and the resistivity of the positive electrode material layer decreases, otherwise it increases; when other parameters remain unchanged, the content of the first carbon nanotube increases, and the resistivity of the positive electrode material layer decreases, otherwise it increases; when other parameters remain unchanged, the content of the second conductive agent increases, and the resistivity of the positive electrode material layer decreases, otherwise it increases; when other parameters remain unchanged, the conductivity of the positive electrode active material increases, and the resistivity of the positive electrode material layer decreases, otherwise it increases.
[0074] The present application has no particular restrictions on the method of regulating the contact impedance of the Rcont peak and the fitting impedance ratio of the Rct peak in the electrochemical impedance spectrum of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the contact impedance of the Rcont peak and the fitting impedance ratio of the Rct peak in the electrochemical impedance spectrum of the positive electrode sheet can be regulated by the content of the first conductive agent, and / or the length, diameter, content, type of the first carbon nanotube, and / or the inorganic particle Dv90, the coating thickness of the first coating, and / or the content and type of the second conductive agent. Specifically, when other parameters remain unchanged, the content of the first conductive agent increases and the ratio decreases, otherwise it increases; when other parameters remain unchanged, the length of the first carbon nanotube increases and the ratio decreases, otherwise it increases; when other parameters remain unchanged, the diameter of the first carbon nanotube increases and the ratio decreases, otherwise it increases; when other parameters remain unchanged, the content of the first carbon nanotube increases and the ratio decreases, otherwise it increases; when other parameters remain unchanged, the content of the second conductive agent increases and the ratio decreases, otherwise it increases; when other parameters remain unchanged, the Dv90 of the inorganic particles increases and the ratio decreases, otherwise it increases; when other parameters remain unchanged, the thickness of the first coating increases and the ratio increases, otherwise it decreases.
[0075] The present application has no particular restrictions on the manner of regulating the bonding force between the first coating and the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the bonding force between the first coating and the positive electrode current collector can be regulated by the inorganic particles Dv90 and the mass percentage of the first binder. Specifically, when other parameters remain unchanged, the inorganic particles Dv90 increase, the bonding force between the first coating and the positive electrode current collector decreases, and vice versa; when other parameters remain unchanged, the mass percentage of the first binder increases, the bonding force between the first coating and the positive electrode current collector increases, and vice versa.
[0076] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet may include but is not limited to the following steps: inorganic particles, a first binder and a third conductive agent are mixed in a mass ratio of (80 to 94.5): (0.5 to 15): (0.7 to 5), deionized water is added as a solvent, and stirred evenly to obtain a first coating slurry with a solid content of 70wt% to 80wt%; then the first coating slurry is coated on one surface of the positive electrode current collector, and baked at 90℃ to 180℃ for 1h to 3h to obtain a first coating. Then prepare the positive electrode material layer slurry: the positive electrode active material, the first conductive agent, and the positive electrode binder are mixed in a mass ratio of (95 to 98): (0.6 to 3): (0.1 to 2), and a solvent is added, and the positive electrode material layer slurry is obtained after being evenly stirred; or the positive electrode active material, the first conductive agent, the second conductive agent, and the positive electrode binder are mixed in a mass ratio of (94 to 97): (0.6 to 3.1): (1.4 to 2.8): (0.1 to 2), and a solvent is added, and the positive electrode material layer slurry is obtained after being evenly stirred. The positive electrode material layer slurry with a solid content of 70wt% to 80wt% is coated on the surface of the first coating layer, and dried to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on one side. Repeat the above steps on the other surface of the positive electrode current collector to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on both sides.
[0077] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0078] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0079] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0080] In some embodiments of the present application, the inorganic layer includes inorganic particles and an inorganic layer binder. The present application has no particular restrictions on the inorganic particles, for example, the inorganic particles may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the inorganic layer binder, for example, the inorganic layer binder may be at least one of the above-mentioned positive electrode binders.
[0081] In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0082] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0083] In the present application, the electrochemical device also includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0084] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.
[0085] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0086] In some embodiments of the present application, the negative electrode material layer may also include a negative electrode conductive agent, a negative electrode binder and a thickener. The present application has no particular restrictions on the types of negative electrode conductive agents, negative electrode binders and thickeners, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF), and / or carbon nanofibers. The above-mentioned metal materials may include but are not limited to metal powders, and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the negative electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. For example, the thickener may include, but is not limited to, at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductor, the negative electrode binder, and the thickener in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0087] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 30 μm to 120 μm.
[0088] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0089] Optionally, the negative electrode sheet may further include a negative electrode conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the negative electrode conductive layer, which may be a conductive layer commonly used in the art. For example, the negative electrode conductive layer includes a negative electrode conductive layer conductive agent and a negative electrode conductive layer binder. The present application has no particular restrictions on the negative electrode conductive layer conductive agent and the negative electrode conductive layer binder, and may be, for example, at least one of the above-mentioned negative electrode conductive agent and the above-mentioned negative electrode binder.
[0090] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0091] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium hexafluorosilicate (LiSiF6), lithium bis(oxalatoborate) (LiBOB) and lithium difluoroborate (LiF2OB). The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.
[0092] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0093] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0094] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0095] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0096] The second aspect of the present application provides an electronic device, which includes the electrochemical device described in the first aspect of the present application. The electronic device of the present application has good nail penetration safety performance, low temperature cycle performance and fast charging performance.
[0097] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0098] Example
[0099] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0100] Test methods and equipment:
[0101] The first carbon nanotube length and diameter test:
[0102] The sample is directly placed in the sample chamber of a scanning electron microscope (OXFORD·EDS), and the length and diameter of the first carbon nanotube are measured by surface observation. The sample surface is observed at different positions, and the magnification is set to 50,000 times to measure the length and diameter of the first carbon nanotube.
[0103] Three different positions are selected to measure the lengths and diameters of all the first carbon nanotubes in the field of view respectively, and the average value is the length and diameter of the first carbon nanotube.
[0104] Ion migration number test of positive electrode material layer:
[0105] The ion migration number test was performed using a CHI660E electrochemical workstation. The lithium-ion battery prepared in the embodiment or comparative example was connected to the test device, a constant voltage of 1V was applied, and the data of the current change over time were recorded for measurement. According to the current-time curve, the formula Calculate the ion migration number, t is the ion migration number, where i t is the stable current value, i0 is the initial current value.
[0106] Thickness test of the first coating and cathode material layer:
[0107] The positive electrode sheet was plasma cut longitudinally along the thickness direction, and a flat cross section was obtained by argon ion polishing technology. Then, a scanning electron microscope (OXFORD·EDS) was used for observation at a magnification of 3000 times. The thickness of 9 positions in the first coating layer was measured at equal intervals along the length direction of the positive electrode sheet, and the average value of the thicknesses at 9 different positions was taken and recorded as the thickness of the first coating layer;
[0108] The positive electrode sheet was plasma cut longitudinally along the thickness direction, and a flat cross section was obtained by argon ion polishing technology. Then, a scanning electron microscope (OXFORD·EDS) was used for observation at a magnification of 1000 times. The thickness of the positive electrode material layer at three positions was measured, and the average value was taken as the thickness of the positive electrode material layer.
[0109] The ratio of the thickness of the first coating layer to the thickness of the positive electrode material layer (%) = the thickness of the first coating layer / the thickness of the positive electrode material layer×100%.
[0110] Particle size test of secondary particles of the third conductive agent:
[0111] The positive electrode sheet was plasma cut longitudinally along the thickness direction, and a flat cross section was obtained by argon ion polishing technology. The secondary particles of the third conductive agent were observed and the particle size was measured within the range of 4 μm×4 μm in the scanning electron microscope image at a magnification of 30,000 times, and the average particle size was recorded as the particle size of the secondary particles of the third conductive agent;
[0112] In the electron microscope test, when the secondary particles cannot be observed at a magnification of 30,000 times, the particle size of the secondary particles is recorded as <50 nm, which indicates that the third conductive agent has good dispersibility.
[0113] Inorganic particle size test:
[0114] Take the positive electrode sheet prepared in the embodiment or comparative example, scrub the positive electrode sheet with N-methylpyrrolidone (NMP) for 5 consecutive times to expose the first coating of the positive electrode sheet, stick the conductive glue on the sample table, lay the treated positive electrode sheet on the conductive glue with the first coating facing up, blow away the unadhered powder with an ear-cleaning bulb, spray gold, and use a Philips XL-30 field emission scanning electron microscope to photograph the surface of the first coating at an acceleration voltage of 10 kV and an emission current of 10 mA. The magnification is 30,000 times, and the surface of the first coating at 5 different positions is photographed. 100 particles are randomly selected from the SEM photos of each position, and the area of each of these particles is calculated. Then, assuming that the particles are spherical, the respective particle sizes D (diameter) are calculated by the following formula: D = 2 × (S1 / π) 1 / 2 ; Wherein, S1 is the area of the particle; the particle size distribution is statistically analyzed to obtain the inorganic particle Dv90.
[0115] Electrochemical impedance spectroscopy (EIS) test:
[0116] The EIS test was performed using a Solartron 1260 electrochemical impedance spectrometer, and the lithium-ion battery prepared in the embodiment or comparative example was connected to the device to ensure good electrode contact. A 5mV AC voltage was applied to the sample with a frequency range from 0.1Hz to 1MHz, and the AC current response was recorded and the impedance spectrum of the positive electrode was obtained.
[0117] By fitting the circuit model, the time domain Fourier transform (DFT) is used for fine decomposition and the contact resistance (Rcont) (peak position at 10 4 ~10 6 Hz) and charge transfer resistance (Rct) (peak position at 10 -1 ~10 1 Hz), the ratio of the above two peak signal intensities, that is, the ratio of the contact impedance of the Rcont peak to the fitting impedance of the Rct peak.
[0118] Diaphragm resistance test:
[0119] Using a two-probe film resistor (BER2500), the test area of the first coating or positive electrode is 154mm 2 , the pressure is 0.4T.
[0120] After using DMC to scrub and remove the surface insulation, the positive electrode sheet is directly tested to obtain the film resistance of the positive electrode sheet;
[0121] The positive electrode plate was scrubbed with NMP for 5 consecutive times to expose the surface of the first coating layer. The first coating layer was tested to obtain the sheet resistance of the first coating layer.
[0122] Resistivity test of positive electrode material layer:
[0123] The needles of four probes are arranged in a straight line at equal distances and are respectively recorded as probes 1, 2, 3, and 4. The radius of curvature of the probe tips is 25 μm, and the probe spacing is fixed at 1 mm. A pressure of 150 g is applied between the probes and the positive electrode material layer, and the penetration depth is 2 μm. The voltage V and current value I are obtained by the voltmeter and ammeter, and the square resistance of the positive electrode material layer is calculated to be (π / ln2)×(V / I), where π is pi.
[0124] The resistivity of the positive electrode material layer = the square resistance of the positive electrode material layer / the penetration depth of 2 μm.
[0125] Adhesion test between the first coating and the positive electrode current collector:
[0126] Take the positive electrode sheet coated with the first coating, the sample size is 15mm×250mm. Use double-sided tape to stick the positive electrode sheet on a smooth steel plate, stick the other side of the positive electrode sheet with adhesive tape, and fix one end of the adhesive tape on a tensile tester (Instron5982), set the speed to 10mm / min, and use the tensile tester to pull the adhesive tape straight at 180°, read the adhesive force when the adhesive tape is stretched, and export the data and divide it by the width of the adhesive tape 15mm to obtain the adhesive force between the first coating and the positive current collector.
[0127] Nail penetration test pass rate:
[0128] Take 50 lithium-ion batteries prepared in the embodiment or comparative example and fully charge them at 25±3°C. The specific steps are: charge at a constant current of 0.5C to 4.5V, and then charge at a constant voltage of 4.5V to a current cutoff of 0.05C.
[0129] The lithium-ion battery was subjected to a nail penetration test at 25±3℃, using a steel nail with a diameter of 4mm, made of carbon steel, with a taper of 16.5mm, and a total length of 100mm. The nail penetration speed was set to 30mm / s, and the nail penetration depth was based on the taper of the steel nail passing through the lithium-ion battery. The state of the lithium-ion battery was observed during the test, and the judgment standard was that the lithium-ion battery did not burn or explode. The nail penetration test pass rate (%) = the number of nail penetration tests passed / 50×100%.
[0130] First charging time test:
[0131] The lithium-ion battery was charged at 3C constant current to 4.5V at 25±3℃, and then charged at 4.5V constant voltage to a current of 0.05C. The time from the start of charging to the end of charging was calculated and recorded as the time of the first charge.
[0132] Low temperature cycle performance test
[0133] After the lithium-ion battery is placed in a 25℃±3℃ environment for 30 minutes, it is charged to 4.2V at a constant current of 1.25C, then charged to 4.5V at a constant current of 1.5C, then charged to 0.05C at a constant voltage of 4.5V, and discharged to 3.0V at a constant current of 0.2C, which is recorded as capacity 1. Repeat the above full charging process, and then transfer to a -20℃±3℃ environment and place it for 30 minutes. Discharge to 3.0V at a constant current of 0.2C, which is recorded as capacity 2. The ratio of capacity 2 to capacity 1 is used to obtain the low-temperature cycle capacity retention rate (%);
[0134] 45℃ Cyclic Performance Test:
[0135] After the lithium-ion batteries of Example 1-1, Comparative Example 2, and Comparative Example 6 were left standing for 30 minutes in an environment of 45°C±3°C, they were charged to 4.25V at a constant current of 1.25C, then charged to 4.5V at a constant current of 1.5C, then charged to 0.05C at a constant voltage of 4.5V, left standing for 30 minutes, and then discharged to 3.0V at a constant current of 0.7C. The discharge capacity obtained in this step was the initial capacity. Repeat the above cycle, and at the 50th cycle, left standing for 30 minutes, and then discharged to 3.0V at a constant current of 0.2C;
[0136] Repeat the above cycle. When the cycle reaches the 100th cycle, let it stand for 30 minutes, and then discharge it to 3.0V at a constant current of 0.2C.
[0137] Repeat the above cycle. When the cycle reaches the 150th cycle, let it stand for 30 minutes, and then discharge it to 3.0V at a constant current of 0.2C.
[0138] Repeat the above cycle. When the cycle reaches the 200th cycle, let it stand for 30 minutes, and then discharge it to 3.0V at a constant current of 0.2C.
[0139] Repeat the above cycle. When the cycle reaches the 250th cycle, let it stand for 30 minutes, and then discharge it to 3.0V at a constant current of 0.2C.
[0140] Repeat the above cycle. When the cycle reaches the 300th cycle, let it stand for 30 minutes, and then discharge it to 3.0V at a constant current of 0.2C.
[0141] Repeat the above cycle. When the cycle reaches the 350th cycle, let it stand for 30 minutes, and then discharge it to 3.0V at a constant current of 0.2C.
[0142] Repeat the above cycle. When the cycle reaches the 400th cycle, let it stand for 30 minutes, and then discharge it to 3.0V at a constant current of 0.2C.
[0143] The discharge capacity at cycle 0, 50, 100, 150, 200, 250, 300, 350 and 400 was compared with the initial capacity to obtain the discharge capacity retention rate at each step, and the cycle capacity retention rate graph of the lithium-ion battery at 45°C±3°C was recorded.
[0144] 1s DC internal resistance test method:
[0145] 1) The test environment temperature is 25±3℃, the lithium-ion battery is charged at a constant current of 0.5C to 4.5V, then charged at a constant voltage of 4.5V to a current of 0.05C, and left to stand for 30 minutes;
[0146] 2) Discharge the lithium-ion battery at 1C for 1s;
[0147] 3) The voltage drop in the process of 2) is measured as △U, and the current is measured as I;
[0148] 4) Then the DC internal resistance of a lithium-ion battery when discharged at 1C for 1s = △U / I.
[0149] Lithium-ion battery internal resistance test:
[0150] The lithium-ion batteries of Example 1-1, Comparative Example 2, and Comparative Example 6 were charged to 4.5V at a constant current of 0.5C, then charged to a current of 0.05C at a constant voltage of 4.5V, left to stand for 30 minutes, and then charged to a current of 0.05C at a constant voltage of 4.5V. The AC internal resistance of the lithium-ion batteries was tested using a Hioki BT4560 battery impedance meter, with the measurement frequency set to 1kHz and the disturbance voltage set to 5mV. The test value was recorded as the initial internal resistance, and the above cycle was repeated until 800 cycles;
[0151] The internal resistance of the lithium-ion battery after each cycle is obtained by measuring the internal resistance after 0, 1, 50, 100, 150, 200, 300, 400, 500, 600, 700 and 800 cycles.
[0152] Example 1-1
[0153] <Preparation of positive electrode sheet>
[0154] The inorganic nano-boehmite particles (Dv90 is 500nm), the first binder sodium polyacrylate and the third conductive agent Ketjen black are mixed in a mass ratio of 89:9:2, deionized water is added as a solvent, and the first coating slurry with a solid content of 75wt% is obtained by stirring evenly, and the first coating slurry is dispersed by ball milling for 25 times, and coated on one surface of a 10μm positive electrode current collector aluminum foil, and baked at 120°C for 2 hours to obtain a positive electrode current collector with a surface coated with the first coating. Then repeat the above steps on the other surface of the positive electrode current collector aluminum foil.
[0155] The positive electrode active material lithium cobalt oxide, the first conductive agent, the second conductive agent, and the positive electrode binder polyvinylidene fluoride are mixed in a mass ratio of 94.6:1.6:2:1.8, the first conductive agent includes the first SWCNTs and the second SWCNTs, the first SWCNTs are SWCNTs, the second SWCNTs are SWCNTs, and the second conductive agent is acetylene black. NMP is added as a solvent, and the mixture is stirred evenly in a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry is evenly coated on the surface of the first coating away from the positive electrode current collector, and dried at 120°C to obtain a positive electrode sheet coated with the first coating and the positive electrode material layer on one side, and the coating weight of the positive electrode material layer is 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet with a first coating and a positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. The compaction density of the positive electrode sheet is 4.23g / cm 3 .
[0156] The thickness of the first coating layer is 0.8 μm, the thickness of the single-sided positive electrode material layer is 90 μm, and the ratio of the thickness of the single-sided positive electrode material layer to the thickness of the first coating layer is 0.89%;
[0157] In the positive electrode material layer, the first conductive agent includes first SWCNTs and second SWCNTs, and the mass percentage of the first conductive agent is 1.6%. Among them, the mass percentage of the first SWCNTs is 1%, the length of the first SWCNTs is 3μm, and the tube diameter is 50nm; the mass percentage of the second SWCNTs is 0.6%, the length of the second SWCNTs is 500nm, and the tube diameter is 20nm. In the positive electrode material layer, the mass percentage of the second conductive agent is 2%.
[0158] <Preparation of negative electrode sheet>
[0159] The negative electrode active material artificial graphite, the negative electrode conductive agent acetylene black, and the negative electrode binder carboxymethyl cellulose (CMC) were mixed in a mass ratio of 97.7:1:1.3, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70wt%, and the negative electrode slurry was obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. Among them, the thickness of the single-sided negative electrode material layer is 90.3μm, and the compaction density is 1.75g / cm 3 .
[0160] <Preparation of Electrolyte>
[0161] In an argon atmosphere glove box with a water content of less than 10 ppm, carbonate compounds ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) are uniformly mixed in a mass ratio of 10:30:60 to obtain a base solvent, and lithium salt LiPF6 is added and stirred to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the base solvent.
[0162] <Isolation film>
[0163] A polyethylene porous polymer film with a thickness of 8 μm (manufacturer: Celgard Membrane Co., Ltd., USA) was used as a separator.
[0164] <Preparation of lithium-ion batteries>
[0165] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound, and the electrode assembly is placed in an aluminum-plastic film shell, and the water is removed at 80°C, and the prepared electrolyte is injected, and the lithium-ion battery is obtained after vacuum packaging, standing, forming, and shaping. Among them, the upper limit voltage of the formation is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.
[0166] Example 1-2 to Example 1-16
[0167] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1-1. When the mass percentage of the first conductive agent and / or the second conductive agent changes, the mass percentage of the positive electrode active material changes accordingly, the mass percentage of the positive electrode binder remains unchanged, and the mass percentage of each substance in the positive electrode material layer is 100%.
[0168] Example 2-1 to Example 2-16
[0169] Except for adjusting the corresponding preparation parameters according to Table 3, the rest is the same as Example 1-1. In the <Preparation of Positive Electrode Sheet> of Example 2-16, ball milling dispersion is not performed, so that the particle size of the secondary particles of the third conductive agent is as shown in Table 1.
[0170] Comparative Example 1
[0171] <Preparation of positive electrode sheet>
[0172] The inorganic particle nano-boehmite (Dv90 is 500nm), the first binder sodium polyacrylate and the third conductive agent Ketjen black are mixed in a mass ratio of 89:9:2, deionized water is added as a solvent, and the mixture is stirred evenly to obtain a first coating slurry with a solid content of 75wt%, which is then coated on one surface of a 10μm positive electrode current collector aluminum foil, and baked at 120°C for 2 hours to obtain a positive electrode current collector with the first coating coated on the surface.
[0173] The positive electrode active material lithium cobalt oxide, the second conductive agent, and the positive electrode binder polyvinylidene fluoride are mixed in a mass ratio of 96:2:2, the second conductive agent is acetylene black, NMP is added as a solvent, and the mixture is stirred evenly in a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry is evenly coated on the surface of the first coating layer away from the positive electrode current collector, and dried at 120°C to obtain a positive electrode sheet with a single-sided coating of the first coating layer and the positive electrode material layer, and the coating weight of the positive electrode material layer is 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet with a first coating and a positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. The compaction density of the positive electrode sheet is 4.23g / cm 3 .
[0174] The thickness of the first coating layer is 0.8 μm, the thickness of the single-sided positive electrode material layer is 90 μm, and the ratio of the thickness of the single-sided positive electrode material layer to the thickness of the first coating layer is 0.89%;
[0175] In the positive electrode material layer, the mass percentage of the second conductive agent is 2%.
[0176] Comparative Example 2 to Comparative Example 5
[0177] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0178] Comparative Example 6
[0179] Except that the first coating layer is not provided in <Preparation of positive electrode sheet>, the rest is the same as Example 1-1.
[0180] The preparation parameters and properties of each embodiment and comparative example are shown in Tables 1 to 4.
[0181] Table 1
[0182]
[0183] Note: “ / ” in Table 1 indicates that there is no corresponding preparation parameter, substance or performance parameter.
[0184] Table 2
[0185]
[0186] The length, diameter and ion migration number of the first carbon nanotube in the positive electrode material layer will affect the nail penetration safety performance, low temperature cycle performance and fast charging performance of the electrochemical device. From Example 1-1 to Example 1-16 and Comparative Example 1 to Comparative Example 6, it can be seen that when the length, diameter and ion migration number of the first carbon nanotube and the positive electrode material layer are within the scope of the present application, the prepared lithium ion battery has a higher puncture test pass rate, a shorter first charge time, a lower 1s DC internal resistance and a higher low temperature capacity retention rate, indicating that the nail penetration safety performance, low temperature cycle performance and fast charging performance of the lithium ion battery prepared in the embodiment of the present application are improved.
[0187] The film resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet, and the fitted impedance ratio of the Rct peak will be affected by the length, diameter, mass percentage, type of the first carbon nanotube, and / or the mass percentage of the first conductive agent, and / or the mass percentage and type of the second conductive agent. It can be seen from Examples 1-1 to 1-16 that the length, diameter, mass percentage, type of the first carbon nanotube, and / or the mass percentage of the first conductive agent, and / or the mass percentage and type of the second conductive agent are within the scope of this application, and the film resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, and the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application.
[0188] like Figure 2 As shown, the surface morphology of the first coating layer prepared in Example 1-1 of the present application is shown. The inorganic particles of the first coating layer form a dense coating layer on the surface of the positive electrode current collector and are evenly dispersed.
[0189] like Figure 3 , which is a cross-sectional view of the positive electrode sheet prepared in Example 1-1 of the present application along the thickness direction, Figure 3 The middle part is the positive electrode current collector. Figure 3 The positive electrode material layer and the positive electrode active material particles in the positive electrode material layer are located above and below the positive electrode, and the first coating layer is located between the positive electrode material layer and the positive electrode current collector.
[0190] like Figure 4As shown, the lithium ion batteries prepared in Example 1-1 and Comparative Example 6 have a higher cycle capacity retention rate at 45°C, while the cycle capacity retention rate at 45°C of Comparative Example 2 is lower. Among them, since Comparative Example 6 does not have a first coating, its puncture test pass rate is 0%, indicating that the lithium ion battery prepared in Comparative Example 6 has poor nail penetration safety performance.
[0191] like Figure 5 As shown, the AC impedance of the lithium ion batteries prepared in Example 1-1 and Comparative Example 6 is low, and the AC impedance of Comparative Example 2 is high. Among them, since Comparative Example 6 does not have a first coating, its puncture test pass rate is 0%, indicating that the lithium ion battery prepared in Comparative Example 6 has poor nail penetration safety performance.
[0192] like Figure 6 As shown, it is the EIS spectrum of the positive electrode sheets prepared in Example 1-1 and Comparative Example 1 and Comparative Example 6 in the present application. The ratio of the contact impedance of the Rcont peak and the fitting impedance of the Rct peak in the EIS spectrum of the positive electrode sheet in Example 1-1 is within the scope of the present application. At the same time, the diaphragm resistance and the resistivity of the positive electrode material layer of Example 1-1 are also within the scope of the present application. The lithium-ion battery prepared in Example 1-1 has good nail penetration safety performance, fast charging performance and cycle performance.
[0193] The mass percentage of the first carbon nanotube and the first conductive agent will affect the nail penetration safety performance, low temperature cycle performance and fast charging performance of the electrochemical device. It can be seen from Examples 1-1, 1-5 to 1-7 that the mass percentage of the first carbon nanotube and the first conductive agent is within the scope of this application, the membrane resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, the prepared lithium-ion battery has a high puncture test pass rate, a short first charge time, a low 1s DC internal resistance, and a high low temperature capacity retention rate, indicating that the lithium-ion battery prepared in the examples of this application has good nail penetration safety performance, low temperature cycle performance and fast charging performance.
[0194] The material of the first carbon nanotube will affect the nail penetration safety performance, low temperature cycle performance and fast charging performance of the electrochemical device. From Example 1-1 and Example 1-12, it can be seen that the material of the first carbon nanotube is within the scope of this application, the film resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, and the prepared lithium-ion battery has a high puncture test pass rate, a short first charge time, a low 1s DC internal resistance, and a high low temperature capacity retention rate, indicating that the nail penetration safety performance, low temperature cycle performance and fast charging performance of the lithium-ion battery prepared in the examples of this application are improved.
[0195] The mass percentage and material of the second conductive agent will affect the nail penetration safety performance, low temperature cycle performance and fast charging performance of the electrochemical device. From Example 1-1, Example 1-13 to Example 1-16, it can be seen that the mass percentage and material of the second conductive agent are within the scope of this application, the film resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, the prepared lithium-ion battery has a high puncture test pass rate, a short first charge time, a low 1s DC internal resistance, and a high low temperature capacity retention rate, indicating that the nail penetration safety performance, low temperature cycle performance and fast charging performance of the lithium-ion battery prepared in the examples of this application are improved.
[0196]
[0197]
[0198] The Dv90 of the inorganic particles in the first coating will affect the nail penetration safety performance, low-temperature cycle performance and fast charging performance of the electrochemical device. From Example 1-1, Example 2-1 to Example 2-5, it can be seen that the Dv90 of the inorganic particles is within the scope of this application, the diaphragm resistance of the first coating, the diaphragm resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, the prepared lithium-ion battery has a high puncture test pass rate, a short first charging time, a low 1s DC internal resistance, and a high low-temperature capacity retention rate, indicating that the lithium-ion battery prepared in the examples of this application has good nail penetration safety performance, low-temperature cycle performance and fast charging performance.
[0199] The mass percentage and type of inorganic particles, the first binder, and the third conductive agent in the first coating will affect the nail penetration safety performance, low-temperature cycle performance, and fast charging performance of the electrochemical device. From Example 1-1, Example 2-6 to Example 2-11, it can be seen that the mass percentage and type of inorganic particles, the first binder, and the third conductive agent in the first coating are within the scope of this application, the diaphragm resistance of the first coating, the diaphragm resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, and the prepared lithium-ion battery has a high pass rate in the puncture test, a short first charging time, a low 1s DC internal resistance, and a high low-temperature capacity retention rate, indicating that the lithium-ion battery prepared in the embodiment of this application has good nail penetration safety performance, low-temperature cycle performance, and fast charging performance.
[0200] The thickness of the first coating will affect the nail penetration safety performance, low-temperature cycle performance and fast charging performance of the electrochemical device. From Example 1-1, Example 2-12 to Example 2-15, it can be seen that the thickness of the first coating is within the scope of this application, the diaphragm resistance of the first coating, the diaphragm resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, and the prepared lithium-ion battery has a high puncture test pass rate, a short first charge time, a low 1s DC internal resistance, and a high low-temperature capacity retention rate, indicating that the lithium-ion battery prepared in the examples of this application has good nail penetration safety performance, low-temperature cycle performance and fast charging performance.
[0201] The particle size of the secondary particles of the third conductive agent will affect the nail penetration safety performance, low temperature cycle performance and fast charging performance of the electrochemical device. From Example 1-1 and Example 2-16, it can be seen that the particle size of the secondary particles of the third conductive agent is within the scope of this application, the diaphragm resistance of the first coating, the diaphragm resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, the prepared lithium-ion battery has a high pass rate for the puncture test, a short first charge time, a low 1s DC internal resistance, and a high low temperature capacity retention rate, indicating that the lithium-ion battery prepared in the examples of this application has good nail penetration safety performance, low temperature cycle performance and fast charging performance.
[0202] The ratio of the thickness of the first coating layer to the thickness of the positive electrode material layer will affect the nail penetration safety performance, low temperature cycle performance and fast charging performance of the electrochemical device. From Example 1-1, Example 2-12, and Example 2-15, it can be seen that the ratio of the thickness of the first coating layer to the thickness of the positive electrode material layer is within the scope of this application, the diaphragm resistance of the first coating layer, the diaphragm resistance of the positive electrode sheet, the resistivity of the positive electrode material layer, the contact impedance of the Rcont peak in the electrochemical impedance spectrum of the positive electrode sheet and the fitted impedance ratio of the Rct peak are within the scope of this application, and the prepared lithium-ion battery has a high pass rate in the puncture test, a short first charge time, a low 1s DC internal resistance, and a high low temperature capacity retention rate, indicating that the lithium-ion battery prepared in the examples of this application has good nail penetration safety performance, low temperature cycle performance, and fast charging performance.
[0203] The bonding force between the first coating and the positive electrode current collector is affected by the mass percentage of the inorganic particles Dv90 and the first binder. From Examples 1-1, 2-1 to 2-8, it can be seen that the mass percentage of the inorganic particles Dv90 and the first binder is within the range of this application, and the bonding force between the first coating and the positive electrode current collector is within the range of this application.
[0204] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0205] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0206] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0207] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0208] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
Claims
1. An electrochemical device, comprising a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector, a first coating and a positive electrode material layer, the first coating being disposed on a surface of the positive electrode current collector, and the positive electrode material layer being disposed on a surface of the first coating away from the positive electrode current collector; The first coating layer includes inorganic particles, and the inorganic particles include at least one of nano-boehmite, aluminum oxide, titanium dioxide, magnesium oxide, zirconium oxide or zinc oxide; The positive electrode material layer includes a first conductive agent, which includes a first carbon nanotube; the length of the first carbon nanotube is 2 μm to 5 μm, and the diameter of the first carbon nanotube is 2 nm to 100 nm; the ion migration number of the positive electrode material layer is 0.4 to 0.
47.
2. The electrochemical device according to claim 1, wherein: The electrochemical device satisfies at least one of the following conditions: (1) The length of the first carbon nanotube is 2 μm to 4 μm; (2) The diameter of the first carbon nanotube is 20 nm to 80 nm.
3. The electrochemical device according to claim 1, wherein Based on the mass of the positive electrode material layer, the mass percentage of the first carbon nanotubes is 0.5% to 2.5%.
4. The electrochemical device according to claim 1, wherein Based on the mass of the positive electrode material layer, the mass percentage of the first conductive agent is 0.6% to 3.1%.
5. The electrochemical device according to claim 1, wherein The positive electrode material layer further includes a second conductive agent, which includes at least one of conductive carbon black or activated carbon; based on the mass of the positive electrode material layer, the mass percentage of the second conductive agent is 1.4% to 2.8%.
6. The electrochemical device according to claim 1, wherein The first coating layer further includes a first binder and a third conductive agent, and the Dv90 of the inorganic particles is 200nm to 1000nm.
7. The electrochemical device according to claim 1, wherein: The thickness of the first coating layer is 0.2 μm to 2 μm.
8. The electrochemical device according to any one of claims 6 to 7, wherein: The electrochemical device satisfies at least one of the following conditions: (1) The Dv90 of the inorganic particles is 400nm to 600nm; (2) The thickness of the first coating layer is 0.5 μm to 1.25 μm.
9. The electrochemical device according to claim 7, wherein: The ratio of the thickness of the first coating layer to the thickness of the positive electrode material layer is 0.18% to 2.2%.
10. The electrochemical device according to claim 6, wherein: Based on the mass of the first coating layer, the mass percentage of the inorganic particles is 80% to 94.5%.
11. The electrochemical device according to claim 6, wherein: The first binder includes a water-soluble polymer metal salt; based on the mass of the first coating layer, the mass percentage of the first binder is 0.5% to 15%.
12. The electrochemical device according to claim 11, wherein The metal element in the water-soluble polymer metal salt includes at least one of lithium, sodium, potassium, rubidium, cesium, francium, beryllium, barium, strontium, calcium, or magnesium; the polymer in the water-soluble polymer metal salt includes at least one of polyacrylic acid, carboxymethyl cellulose, polyacrylonitrile, or styrene butadiene.
13. The electrochemical device according to claim 11, wherein The water-soluble polymer metal salt includes at least one of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, calcium polyacrylate, magnesium polyacrylate, rubidium polyacrylate, cesium polyacrylate, francium polyacrylate, barium polyacrylate, strontium polyacrylate, lithium carboxymethyl cellulose, beryllium carboxymethyl cellulose or sodium carboxymethyl cellulose.
14. The electrochemical device according to claim 6, wherein: The third conductive agent includes at least one of conductive carbon black, activated carbon, carbon nanotubes or carbon nanofibers; based on the mass of the first coating, the mass percentage of the third conductive agent is 0.7% to 5%.
15. The electrochemical device according to claim 6, wherein: In the scanning electron microscope image of the first coating at a magnification of 30,000 times, within a range of 4 μm×4 μm, the particle size of the secondary particles of the third conductive agent is less than 50 nm.
16. The electrochemical device according to claim 1, wherein The bonding force between the first coating layer and the positive electrode current collector is 500 N / m to 900 N / m.
17. The electrochemical device according to claim 1, wherein: The electrochemical device satisfies at least one of the following conditions: (1) The sheet resistance of the first coating layer is 200Ω to 2500Ω; (2) In the electrochemical impedance spectrum of the positive electrode sheet, the characteristic frequency is between 10 4 Hz to 10 6 There is an Rcont peak in the Hz range, with a characteristic frequency of 10 -1 There is an Rct peak in the range of Hz to 10Hz, and the ratio of the contact impedance of the Rcont peak to the fitting impedance of the Rct peak is 10 -5 to 0.01; (3) The film resistance of the positive electrode sheet is 1Ω to 3Ω; (4) The resistivity of the positive electrode material layer is 1.125×10 -5 Ω·cm to 1.875×10 -5 Ω·cm.
18. An electronic device comprising the electrochemical device according to any one of claims 1 to 17.
Citation Information
Patent Citations
Positive electrode sheet, secondary battery, and electronic device
CN116111101A
Electrochemical device and electronic device
CN117832589A
Isolating membrane, preparation method thereof, and related secondary battery and electric device
CN119256442A
Separator, secondary battery, and electric device
WO2024174170A1
Cited By
Secondary battery and electronic device
CN120978080A
Secondary battery and electronic device
CN120978080B
Secondary battery and electronic apparatus
EP4811462A1
Electrochemical device and electronic device
WO2026149016A1